Dvouexpresní systémy se zaměřením na parazitická protozoa - Gromyko, Anastasiia (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2023)
Protozoan parasite infections continue to pose a significant health challenge in developing countries, resulting in hundreds of thousands of deaths each year. These parasites exhibit a complex multi-stage life cycle and possess unique cellular structures. However, many of their biological processes remain poorly understood. Multigene expression is a promising approach to address this knowledge gap, as it enables the expression of functional protein complexes in vivo, the addition of fluorescent protein tags for visualization of protein localization within the cell, and the study of protein-protein interactions. This bachelor's thesis reviews the current knowledge on available systems and approaches for studying key model parasitic protozoan species. Keywords: expression systems, Trypanosoma brucei, Leishmania tarentolae, Entamoeba histolytica, Giardia intestinalis, Trichomonas vaginalis, Toxoplasma gondii, Plasmodium falciparum, pET-Duet, CRISPR-Cas9
Keywords: expression systems; expresní systémy; Leishmania tarentolae; Trichomonas vaginalis; Trypanosoma brucei; Plasmodium falciparum; pET-Duet; CRISPR-Cas9; Entamoeba histolytica; Giardia intestinalis; Toxoplasma gondii